PERAN UKURAN PERUSAHAAN, LEVERAGE, PROFITABILITAS DAN KEPEMILIKAN MANAJERIAL TERHADAP EARNING MANAGEMENT (Media Riset Akuntansi, 2022)
This study aims to determine the effect of the role of firm size, leverage, profitability and managerial ownership on earning management. The sample used in this study were manufacturing companies in the mining sector on the Indonesia Stock Exchange (IDX) in 2013-2016, with 36 samples. The method used in this research is multiple linear regression analysis. The results showed that firm size had no effect on earnings management, leverage had no effect on earnings management, profitability had no effect on earnings management and managerial ownership had no effect on earnings management.